Strategic adaptabilty and firm performance : an empirical study of the miles and show typology - Boey, Stephanie Lai Fong (2015)
The motivations behind this study are to gain a deeper understanding and further insights on the Miles and Snow typology as well as to determine the applicability of the typology to Singapore's context. The primary objective of the study is to analyse the relationship between the four strategic types (Prospector, Defender, Analyser and Reactor}, as proposed by Miles and Snow ( 1978}, and company performance. A mail survey was conducted among 330 companies drawn from various industries in Singapore. 65 companies responded to the survey. In classifying organisations into the four strategic types, two approaches were used - paragraph descriptions and eleven-item scale. Performance results were measured based on performance indicators like Return on Investment (ROI) and Market Share. Investment decisions were measured using two dimensions : Timing of Investment and Breadth of Investment. The environment was assessed by looking at the degree of volatility or rate of change in the industry which the organisation competed in. One of the main findings shows that the performance of organisations differ across strategic types with Analyser performing the best. It was also found that the Analyser strategy has the highest performance in stable environments. This implies that if companies were to be in a stable environment, an appropriate strategy to minimise risk and maximise opportunities for profits would be that of an Analyser. In addition, other findings also show that the Defender is most likely to change its strategy to an Analyser strategy. The underlying implication is that the dynamism of the environment may render the Defender strategy to be less viable over time. Hence, changing to an Analyser strategy may be the next logical move. Further analyses show that most organisations emphasise profitability as a key performance measure with Prospector, Analysers and Reactors ranking net profit to sales as the most important performance indicator. On the other hand, Defenders placed market share as the most important element. Finally, the investment behaviour of the four archetypes is found not to be consistent with Collis' (1990) classification as proposed by Gibbons and Prescott (1993). The study does not provide substantial evidence to support their views. Therefore, further studies are necessary to verify the relationship between the four archetypes and Collis' framework. Other further research suggested include measuring the importance of new product development relative to other more appropriate indicators as well as determining the applicability of the Miles and Snow typology in the Asian economies.